Health advocacy*. (1st February 2017) - Hubinette, Maria; Dobson, Sarah; Scott, Ian; Sherbino, Jonathan
Abstract: In the medical profession, activities related to ensuring access to care, navigating the system, mobilizing resources, addressing health inequities, influencing health policy and creating system change are known as health advocacy. Foundational concepts in health advocacy include social determinants of health and health inequities. The social determinants of health (i.e. the conditions in which people live and work) account for a significant proportion of an individual's and a population's health outcomes. Health inequities are disparities in health between populations, perpetuated by economic, social, and political forces. Although it is clear that efforts to improve the health of an individual or population must consider "upstream" factors, how this is operationalized in medicine and medical education is controversial. There is a lack of clarity around how health advocacy is delineated, how physicians' scope of responsibility is defined and how teaching and assessment is conceptualized and enacted. Numerous curricular interventions have been described in the literature; however, regardless of the success of isolated interventions, understanding health advocacy instruction, assessment and evaluation will require a broader examination of processes, practices and values throughout medicine and medical education. To support the instruction, assessment and evaluation of health advocacy, a novel framework for health advocacy is introduced. This framework was developed for several purposes: defining and delineating different types and approaches to advocacy, generating a "roadmap" of possible advocacy activities, establishing shared language and meaning to support communication and collaboration across disciplines and providing a tool for the assessment of learners and for the evaluation of teaching and programs. Current approaches to teaching and assessment of health advocacy are outlined, as well as suggestions for future directions and considerations.